Identification of chondritic krypton and xenon in Yellowstone gases and the timing of terrestrial volatile accretion - Broadley, Michael W. (Proc Natl Acad Sci U S A, 2020)
Identifying the origin of noble gases in Earth’s mantle can provide crucial constraints on the source and timing of volatile (C, N, H(2)O, noble gases, etc.) delivery to Earth. It remains unclear whether the early Earth was able to directly capture and retain volatiles throughout accretion or whether it accreted anhydrously and subsequently acquired volatiles through later additions of chondritic material. Here, we report high-precision noble gas isotopic data from volcanic gases emanating from, in and around, the Yellowstone caldera (Wyoming, United States). We show that the He and Ne isotopic and elemental signatures of the Yellowstone gas requires an input from an undegassed mantle plume. Coupled with the distinct ratio of (129)Xe to primordial Xe isotopes in Yellowstone compared with mid-ocean ridge basalt (MORB) samples, this confirms that the deep plume and shallow MORB mantles have remained distinct from one another for the majority of Earth’s history. Krypton and xenon isotopes in the Yellowstone mantle plume are found to be chondritic in origin, similar to the MORB source mantle. This is in contrast with the origin of neon in the mantle, which exhibits an isotopic dichotomy between solar plume and chondritic MORB mantle sources. The co-occurrence of solar and chondritic noble gases in the deep mantle is thought to reflect the heterogeneous nature of Earth’s volatile accretion during the lifetime of the protosolar nebula. It notably implies that the Earth was able to retain its chondritic volatiles since its earliest stages of accretion, and not only through late additions.